Unfinished: thoughts left visible - Baum, Kelly; Baum, Kelly; Bayer, Andrea; Bayer, Andrea; Wagstaff, Sheena; Wagstaff, Sheena; Urbanelli, Elisa; Urbanelli, Elisa; Bambach, Carmen (The Metropolitan Museum of Art, 2016)
"This unprecedented book explores the evolving concept of unfinishedness as essential to understanding art movements from the Renaissance to the present. Unfinished presents more than 170 works, created in a variety of media, by artists ranging from Leonardo, Titian, Rembrandt, Turner, and Cézanne to Picasso, Warhol, Twombly, Freud, Richter, and Nauman. What unites these works, across centuries and media, is that each one displays some aspect of being unfinished. Essays and case studies by major contemporary scholars address this key concept from the perspective of both the creator and the viewer, probing the impact that this long artistic trajectory-which can be traced back to the first century-has had on modern and contemporary art. The book explores the degrees to which instances of incompleteness were accidental or intentional, experimental or conceptual. Also included are illuminating interviews with contemporary artists, including Tuymans, Celmins, and Marden, and parallel considerations of the unfinished in literature and film. The result is a multidisciplinary approach and thought-provoking analysis that provide valuable insight into the making, meaning, and critical reception of the unfinished in art"--Distributor's website